2006
DOI: 10.2186/prp.5.231
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Relationship between Palatal Contour and the Phonetic Function in Complete Denture Wearers Using a Speech Recognition System

Abstract: Individuals using dental prosthetic appliances tend to mispronounce the /S/ sound, phonation of which depends on the shape of the palatal contour. Thus, prosthodontists need to create the palatal contour in complete dentures with care. Here, we report that by using a speech recognition system, the palatal contour can be easily adjusted in the waxed denture base. AbstractPurpose: This study used a speech recognition system to investigate the intelligibility of the /S/ sound, which is based on the palatal contou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The speech evaluation system used in this study could assess leaks-in or closure of the vocal tracts by comparing tongue contact areas between the target and emerging sounds, thus identifying the incorrect labels [15, 27, 28]. In this study, the appearance of the [gi] sound as an incorrect label for [ki] significantly increased with the placement of an M-bar in low-palate subjects, compared with high-palate subjects.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The speech evaluation system used in this study could assess leaks-in or closure of the vocal tracts by comparing tongue contact areas between the target and emerging sounds, thus identifying the incorrect labels [15, 27, 28]. In this study, the appearance of the [gi] sound as an incorrect label for [ki] significantly increased with the placement of an M-bar in low-palate subjects, compared with high-palate subjects.…”
Section: Discussionmentioning
confidence: 82%
“…The speech evaluation system (Voice Analyzer; Toshiba Digital Media Engineering Co., Tokyo, Japan) used speech recognition based on 213 types of integrated phonetic segments that represent phonetic features of transitions from one phoneme to another [27]. The flow process of this system is shown in Figure 2.…”
Section: Methodsmentioning
confidence: 99%
“…The speech evaluation system (Voice Analyzer; Toshiba Digital Media Engineering Co., Tokyo, Japan) uses speech recognition based on 213 types of integrated phonetic segments that represent phonetic features and features of transitions from one phoneme to another [30]. The acoustic analysis was performed using a fast Fourier transform that transformed the speech data of eight analytical frames (79 ms) into 64 ms of information (fast Fourier transform parameters).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, this evaluation can be conducted immediately using only a laptop computer with specific software and a headset microphone. With this system, we tried to analyze the influences of the incisal overjet [29] and palatal contour [30] of a maxillary complete denture on alveolar consonants as well as the influence of the position of the major connector in a maxillary removable partial denture on several consonants, in addition to the alveolar consonants [31]. In particular, we found that locating the major connector in the middle area of the palate results in a smaller disturbance than in other areas from the viewpoints of accuracy of phonetic output, a shorter duration of consonants, and the tendency to change to other consonants.…”
Section: Introductionmentioning
confidence: 99%
“…Some patients had a remarkable adaptive capacity after repeating 5-6 key words. Analyzed spectrograms are different by frequency (low or high) of emitted sounds related to the denture changes and oral resonance cavity [ 17 ]. Specific letters were selected because not all the letters can be verified.…”
Section: Discussionmentioning
confidence: 99%